Case report: A report of the complete pathological response of intrahepatic cholangiocarcinoma after conversion therapy - Zhang, Xi; Tang, Hao; Fan, Jun; Wang, Rui; Han, Yunwei; Su, Song; Gan, Yu; Peng, Fangyi; Rao, Mingyue; Zhang, Jianwen; Li, Bo; Yang, Xiaoli (Frontiers in Immunology, 2022)
Cholangiocarcinoma （CCA） is a rare disease with a poor prognosis, and surgery remains the only curative treatment option. However, most patients are not suitable for surgical treatment. Conversion therapy may provide opportunities for the operation of these patients. We report a case of Intrahepatic cholangiocarcinoma （ICC） treated with albumin paclitaxel, cisplatin and gemcitabine in combination with carrelizumab, which was successfully treated with surgery and achieved pathological complete remission. This provides a reference for clinicians to carry out conversion therapy for ICC.